THE RECEPTION OF LITERATURE STUDENTS OF CLASS IVB SDN 25 TOWARD FAIRY TALE ENTITLED “KENDI EMAS DAN ULAR” - Nurulanningsih . (Jurnal Didascein Bahasa, 2018)
One of the literary works that is categorized as children's literature, i.e., a fairy tale. This study describes the reception of literature students class IVb SDN 25 Kilkenny against the fabled Golden Jug (kendi emas) and snakes (ular). This tale is one of 13 fairy tales found in the Thematic book 8 for SD/MI Class IV, works of Ari Subakti. The chosen fairy tale Gold Jug and the snake because it gives moral value of honesty. This literary reception research used the synchronous responses as research method to contemporary readers, meaning that readers are used as respondents in a period of time. The sample in this study was the students of class IVb SDN 25 Palembang that consists of 35 people. The sampling technique used purposive sampling. The data collection techniques in this research apllied question form/questionnaire. The analytical techniques of descriptive statistics was qualitative. Based on the results and discussion toward the reception of literature students of class IVb SDN 25 Palembang toward the fabled Golden Jug and Snake. It can be concluded that admission of students against the good fairy tale story i.e. marked with 54.28% of students responded very efficiently toward such tales and 26.66% of students responded with memorable the fairytales.Keywords: reception, literature, fairy tale.